THE IMPACTS OF COVID-19 PANDEMIC ON CHILD HEALTH CARE - Tavares Lacerda, Priscilla; Rolim de Oliveira, Rafaela; Charllub Pereira Bezerra, Yuri; Silva Oliveira, Geane (Health and Society, 2023)
Objective: Identify the vulnerabilities that occurred to the detriment of the COVID-19 pandemic in child health care. Method: An integrative literature review based on the guiding question: What were the impacts of the COVID-19 pandemic on child health care? Then, a search for articles was carried out in the SCIELO, LILACS, BDENF and BVS databases, between August and November 2022, and five articles were found, using the following descriptors: “pandemic”, “child health care in Brazil” and “covid-19 and child health”, using the Boolean operator AND. The inclusion criteria were: articles available for free and literature reviews published in Portuguese between 2015 and 2022, which delimited Brazil as a study scenario and whose sample involved nurses working in child health care during the pandemic period. Theses, monographs and dissertations were excluded from the study. Results: Due to the large scale contamination by the covid-19 virus, health system took emergency measures to contain the virus, causing health systems to readjust their care model. Because of this, there was a big impact on child heath care, especially with regard to monitoring the child’s growth and development and compliance with child vaccination schedule, bringing deficit effects to the child’s health in a long term. Conclusion: It is necessary to reinforce the lines of care for child health care, as well as the active search for newborns during this period to remedy possible deficits in follow up. In addition to strengthening continuing health education, to reaffirm the partnership between partners or guardians and the health system.